Exploration of Total Flavonoid Content, Toxicity, and Antibacterial Activity of Acorus calamus L. Rhizome Isolates - Jannah, Faridatul; Afriani, Ida Irma; Dewi, Diana Candra; Fasya, A. Ghanaim; Amalia, Suci (The Journal of Pure and Applied Chemistry Research, 2025)
Acorus calamus L. is a medicinal plant with rhizomes commonly used in traditional medicine. This study aimed to determine the total flavonoid content, toxicity, and antibacterial activity of isolates from the rhizome of Acorus calamus L. The rhizome extract was sonicated using 70% ethanol, yielding 18.73% (w/w), and partitioned using ethyl acetate, yielding 10.80% (w/w). Subsequently, the ethyl acetate fraction was further separated using column chromatography. FTIR analysis of the ethanol extract, ethyl acetate fraction, and column isolates confirmed the presence of O–H functional groups and other vibrations, indicating the presence of flavonoid compounds. UV analysis revealed absorption at the band I (302, 302, 383 nm) and band II (253, 254, 258 nm). The total flavonoid content of the isolates, determined using AlCl3, was 32.95 mg QE/g. Liquid Chromatography-Mass Spectrometry (LC-MS) analysis of the column chromatography isolates identified the presence of isorhamnetin, quercetin, genistein, and glycitein. Furthermore, toxicity and antibacterial activity tests on the ethanol extract and ethyl acetate fraction showed LC50 values of 143.53 ppm and 41.16 ppm, respectively, and inhibition zone diameters ranging from 2.30-4.54 mm and 2.63-5.29 mm, respectively.